Solid State Lasers Materials, Technologies and Applications - Federico Pirzio (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Solid-state lasers offer unique qualities in terms of flexibility, robustness, efficiency, and wavelength diversity. For these reasons, they are nowadays irreplaceable tools in many scientific and industrial applications. The engineering of new materials, the advances in photonics technologies, and the increasing demand for speed, cleanliness, and high-precision in industrial processes contribute to propel the research in this exciting and quickly developing field. Despite the impossibility to cover all the aspects of this very diversified topic in a single publication, this Special Issue "Solid State Lasers Materials, Technologies and Applications" offers an interesting insight into some of the latest developments in this field. Comprehensive review papers describe the state of the art of highly doped fiber lasers and amplifiers, deep-ultraviolet generation, and laser welding under vacuum with high-power lasers. Research articles present the latest results on picosecond pulse amplification, mid-infrared laser sources, parametric down-conversion modules, and coherent beam combining. Heavy-industry applications, such as laser welding and laser cladding, are also addressed.